Tryptophan Metabolism Activates Aryl Hydrocarbon Receptor-Mediated Pathway To Promote HIV-1 Infection and Reactivation - Yan-Heng Zhou (American Society for Microbiology, 2019)
ABSTRACT Multiple cellular metabolic pathways are altered by HIV-1 infection, with an impact on immune activation, inflammation, and acquisition of non-AIDS comorbid diseases. The dysfunction of tryptophan (Trp) metabolism has been observed clinically in association with accelerated HIV-1 pathogenesis, but the underlying mechanism remains unknown. In this study, we demonstrated that the aryl hydrocarbon receptor (AHR), a ligand-activated transcription factor, is activated by Trp metabolites to promote HIV-1 infection and reactivation. AHR directly binds to the HIV-1 5′ long terminal repeat (5′-LTR) at the molecular level to activate viral transcription and infection, and AHR activation by Trp metabolites increases its nuclear translocation and association with the HIV 5′-LTR; moreover, the binding of AHR with HIV-1 Tat facilitates the recruitment of positive transcription factors to viral promoters. These findings not only elucidate a previously unappreciated mechanism through which cellular Trp metabolites affect HIV pathogenesis but also suggest that a downstream target AHR may be a potential target for modulating HIV-1 infection. IMPORTANCE Cellular metabolic pathways that are altered by HIV-1 infection may accelerate disease progression. Dysfunction in tryptophan (Trp) metabolism has been observed clinically in association with accelerated HIV-1 pathogenesis, but the mechanism responsible was not known. This study demonstrates that Trp metabolites augment the activation of aryl hydrocarbon receptor (AHR), a ligand-activated transcription factor, to promote HIV-1 infection and transcription. These findings not only elucidate a previously unappreciated mechanism through which cellular Trp metabolites affect HIV pathogenesis but also suggest that a downstream target AHR may be a potential target for modulating HIV-1 infection.